Prevalence, current status, and prevention of dental extractions in dogs: A retrospective study - K Han; Z Piao; C Park; MM Rahman; N Kim (Veterinární Medicína)
Dental health has historically received little attention in veterinary medicine, but is becoming more common. This study aimed to report the prevalence of dental extractions in dogs in Seoul, Republic of Korea, describe the current status of dental health and determine any preventive methods. In total, 166 dogs participated in the study, presented to the veterinary hospital with an oral disorder or for a routine check-up were included in the study. Teeth were extracted from 130 dogs (78.32%). A single tooth was extracted from 18 dogs (13.85%), whereas multiple teeth (2-29 teeth) were extracted from 112 dogs (86.15%). Ten teeth were extracted in 31 dogs (27.67%). In descending order, the most extracted teeth were PM2, PM3, PM4, and PM1. The age at the first dental check-up, the average interval between dental check-ups, and the average interval between the previous two dental check-ups in the extraction group were significantly greater than those in the non-extraction group. In contrast, the number of dental check-ups was significantly lower. In conclusion, this study suggests regular dental check-ups to prevent dental extractions. The data provide useful information for veterinary dental health management and the prevention of tooth extractions.